Baias de atendimento a clientes: produtividade, negociação e experiências dos corpos - Silva, Michel Ferreira da (2020)
The word “baia”, in Brazil,originally defines the confinement space for horses, distancing the animals. Nowadays it went onto refer to the partitions used in the layouts of the global labor market. In North America and parts of Europe they are known as cubicles. In Brazil, they mainly name the workstations designated as Service Points. This study deals with the service industry cubiclesand their meaning effects in the relationship between employee and customer, as well as between employee and company during face-to-face service or by phone, e-mail, WhatsApp, among others. In the 60s, cubicles became a low-cost alternative, subject to customization, primarily among companies with a focus on individual productivity, limiting employee interactions and reducing environmental distractions that could pose risks to the achievement of company goals. Gradually, the service diversified from telemarketing to face-to-face relationships, which motivated the selection of our research object in four spatial situations (in banks, remote service, restaurants and mobile points). In the first three, an organization with greater representation makes up the corpusof this study. They will be analyzed under the methodology of discursive semiotic theory, from participant observation. The foundations are the concept of the generative path of meaning by Greimas and studies by other semioticians on the plane of expression, the regimes of meaning and interaction and the analysis of commercial and ritual spaces, supported respectively by Floch, Landowski and Hammad. Considering that the time spent at work occupies a large part of the human experience and the service materializes commercial relationships, the research reveals the meaning effects of the cubicles, in order to understand how much the syncretic expression in languages of this spatial delimitation produces meaning and which modes of interaction are inscribed in it. The protagonist of this relationship is the service worker who, according to the results of the analyses, is situated as programmed in the thematic role of employee, occasionally exercising some freedom. The cubiclesexcel in productivity, privacy and mimic social relationships in their spatial hierarchy. Recently, its functionality has been extended to isolate citizens in restaurants, schools, beaches, making social distancing as an alternative to contain the spread of COVID-19. Havinggone from commercial spaces to various public spaces, they give new meaning to social relations and are sanctioned as effective in delimiting physical spaces and containing the subjects' bodily movements